The stabilisation properties of immovable property taxation Evidence from OECD countries - Blöchliger, Hansjörg (OECD Economics Department Working Papers, 2015)
This paper contributes to the scarce literature on the macroeconomic effects of property taxes, in particular on the relationships between property taxes, house prices and the wider economy. The paper first estimates a fiscal reaction function which analysis the reaction of property tax revenues to house prices. It then analyses a house price reaction function looking at the relation of how house prices react to changes in property taxes. For a set of OECD countries, the results suggest that property taxes tend to be a-cyclical or slightly pro-cyclical. They provide a stable revenue source for sub-central governments but do not stabilise the economy. The results also suggest that an increase in property tax revenues or in the tax revenue-to-GDP share slows down house price increases and that higher property taxation tends to reduce house price volatility